Update on dexmedetomidine: use in nonintubated patients requiring sedation for surgical procedures - Mohanad Shukry; Jeffrey A Miller (Dove Medical Press, 2010)
Mohanad Shukry, Jeffrey A MillerUniversity of Oklahoma Health Sciences Center, Department of Anesthesiology, Children’s Hospital of Oklahoma, Oklahoma City, OK, USAAbstract: Dexmedetomidine was introduced two decades ago as a sedative and supplement to sedation in the intensive care unit for patients whose trachea was intubated. However, since that time dexmedetomidine has been commonly used as a sedative and hypnotic for patients undergoing procedures without the need for tracheal intubation. This review focuses on the application of dexmedetomidine as a sedative and/or total anesthetic in patients undergoing procedures without the need for tracheal intubation. Dexmedetomidine was used for sedation in monitored anesthesia care (MAC), airway procedures including fiberoptic bronchoscopy, dental procedures, ophthalmological procedures, head and neck procedures, neurosurgery, and vascular surgery. Additionally, dexmedetomidine was used for the sedation of pediatric patients undergoing different type of procedures such as cardiac catheterization and magnetic resonance imaging. Dexmedetomidine loading dose ranged from 0.5 to 5 μg kg-1, and infusion dose ranged from 0.2 to 10 μg kg-1 h-1. Dexmedetomidine was administered in conjunction with local anesthesia and/or other sedatives. Ketamine was administered with dexmedetomidine and opposed its bradycardiac effects. Dexmedetomidine may by useful in patients needing sedation without tracheal intubation. The literature suggests potential use of dexmedetomidine solely or as an adjunctive agent to other sedation agents. Dexmedetomidine was especially useful when spontaneous breathing was essential such as in procedures on the airway, or when sudden awakening from sedation was required such as for cooperative clinical examination during craniotomies.Keywords: dexmedetomidine, sedation, nonintubated patients